INTEGRATING URBANISM AND RELIGIOUS ARCHITECTURE: THE KACHCHHAPAGHATA TEMPLES OF GOPAKSHETRA (10TH-12TH CENTURY AD) - Sinha, Versha; Khare, Ajay (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study explores the evolving progression of temple architecture in the Gopakshetra region during the 10th and 12th centuries AD and its significant influence on the urban landscape of that time. This study examines the modifications adopted by temple builders when responding to evolving parameters and functions. It provides useful insights that can be used to inform current urban transformation initiatives. During this historical period, temples emerged as versatile centers, serving not only as sites of religious worship but also as centers for cultural activities, education, and communal gatherings. They played crucial roles in influencing the social structure and physical layout of historical urban regions. Temple architecture and its purposes underwent changes as urban centers grew and societal needs developed. This study examines several temple placements, temple’s social influence, inscriptions, and architectural elements to demonstrate the evolution of temples over time and their coexistence with the evolving urban environment. The text emphasizes the ability of temples to adjust and meet changing rituals, societal needs, and urban expansion while still maintaining their historical importance. The major findings shed light on the seamless integration of temples in Gopakshetra with their evolving urban setting.